Membuat Jalan Beton Di Tanah Lunak Dengan Metode Cerucuk Kayu Galam - Sulardi Sulardi; Agus Sugianto (Abdimas Universal, 2022)
The problem faced is the difficulty of making the road body on soft soil in the former swamp location. The purpose of community service is to provide technical assistance to make roads on soft soil using simple appropriate technology by utilizing the availability of materials that are cheap and widely found in the market. The working method used is the galam wood chisel method which is installed with a distance of 60 cm and above the cerucuk is installed galam wood girder. The pair of girders and culms of galam wood will then distribute and even out the load on them so that the road body does not experience subsidence and deformation. The results of the improvements made in this community service activity show that the Galam wood cerucuk method is proven to be suitable and suitable to be used to overcome the problem of difficulty in building roads on soft soil. The results of the work that has been done also show that the access road built on soft soil is proven not to be damaged, not cracked, not deformed after being used to serve light vehicle traffic to truck vehicles with loads.